Langmuir probe in ion-beam plasma: theory VS experiment - Dudin, S.V. (Физическая инженерия поверхности, 2012)
The paper is devoted to experimental verification of theoretical model of Langmuir probe operation in ion-beam plasma. The mathematical model of single cylindrical Langmuir probe describes dependence of ion current gathered by the probe on the basic parameters of ion-beam plasma. The model covers wide parameters range of the ion-beam plasma, particularly the whole range typical for technological ion-beam systems. The comparison of the results of numerical calculations with the experimental measurement results confirms high reliability of the model in wide range of parameters excluding the case of very low ion beam energy.